A case of fascioliasis mimicking malignancy (Annals of Medical Research, 2021)
None
Keywords: key. Sometimes,its clinical symptoms may mimic and resemble those of other diseases,such as malignancy or stone. Fascioliasis, initially considered as malignancy, can lead to unnecessary invasive procedures. A 69-year-old man presented with hepatic masses. Positron emission tomography (PET/CT), upper gastrointestinal endoscopy and colonoscopy performed to detect the primary tumour showed no lesion, except in the liver. The patient had eosinophilia and a history of raising livestock in an endemic area. The result of the indirect hemagglutination test for Fasciolia hepatica was 1/320. Serologic evaluation and dynamic computed tomography confirmed the diagnosis. Occassionally, it may be difficult to differentiate fascioliasis from malignancy. Fascioliasis should be considered in the differential diagnosis of patients with suspicious masses in the liver, especially in those living in endemic areas,prior to conducting invasive procedures.br / Fasciola hepatica; fascioliasis; malignancy.